A method for measuring the bending and torsional stiffness distributions of alpine skis - Truong, J.; Brousseau, C.; Desbiens, A. L. (Procedia Engineering, 2016)
A novel non-destructive method for quickly, accurately and simultaneously measuring the bending and torsional stiffness distributions of an alpine ski is presented. This method, named SMAD (Stiffness Measurement through Angular Deformations), is based on measuring the angular deformations resulting from a known combined bending and torsion load. The method's accuracy and repeatability is investigated and are on average under 2% and 3%, respectively. The coupling in the measurement of the bending and torsional deformations during combined loading due to ski misalignment in the test machine is investigated. The measured torsional deformation was found to be independent of the bending load. The measured bending deformation was found to be dependent on the torsional load but this effect could be limited by careful alignment of the ski in the test machine.